PENGARUH PENDEKATAN MINDFUL LEARNING TERHADAP HASIL BELAJAR AQIDAH AKHLAK SISWA KELAS VIII DI MTS TAMAN PENDIDIKAN ISLAM MEDAN TAHUN AJARAN 2019/2020 - Sitopu, Widia Fitriani (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
This study aims to determine whether there are influences on student activities and learning outcomes through the mindful learning approach (awareness in learning) in the subjects of the Islamic Moral Class VIII MTs. Islamic education park in Amplas Medan. This type of research is the Classroom Action Research (CAR) carried out caloboratively between researchers and teachers. Data collection techniques used in this study were the method of observation, interviews, documentation, and learning achievement tests. Based on research that is done in MTs. Islamic Education Park shows the percentage of students who learn in the first cycle with the category of observation: 1. Pay attention to the teacher's explanation 83.63%, 2. Ask 76 76% learning material 3. Exchange opinions with friends 80.00% 4. Put out ideas in discussions 78.18% 5. Working together in groups 81.81%. Of the five categories of student learning activities reached an average of 79.961%. From the results of observations of student learning activities can not be said to be successful, because it has not yet reached the indicator of success set in student learning activities that is ≥ 75%. Then after the action is carried out, based on the results of data analysis it is known that, learning by applying the Mindful Learning approach has an impact on student learning outcomes that have increased. This can be seen from the increase in student learning completeness, and it can be concluded that through the application of the Mindful Learning approach, there is a better improvement from Silkus I to the Second cycle. The percentage of results in the first cycle of 69.10% increased in the second cycle of 89.10%. Therefore, an increase in student learning outcomes in cycle II shows that learning using the Mindful Learning model has succeeded in increasing student learning.